Health Risks and Concerns Associated with E-cigarettes (ECs) and Heated Tobacco Products (HTPs): A Comprehensive Review - Muengtaweepongsa, Sombat (Asian Medical Journal and Alternative Medicine, 2023)
E-cigarettes (ECs) and heated tobacco products (HTPs) are alternative products to traditional cigarettes that operate on different principles. While ECs heat a liquid to produce an aerosol, HTPs heat processed tobacco sticks or cartridges. ECs and HTPs carry potential health risks, and their long-term effects are still being studied. Concerns exist regarding their use among specific populations, including youth and non-smokers. ECs liquids typically contain solvents, flavorings, nicotine, and additives. Heating the liquid can generate aerosols containing potentially harmful substances like formaldehyde, acrolein, heavy metals, phenolic compounds, and polycyclic aromatic hydrocarbons (PAHs). Studies have linked ECs use to increased respiratory symptoms, asthma-related school absenteeism, and chronic respiratory disorders in adolescents and adults. However, clinical trial results investigating respiratory changes from ECs exposure have been inconsistent. The e-cigarette or vaping product use-associated lung injury (EVALI) outbreak raised concerns about acute respiratory risks associated with its use. Evidence suggests a potential association between ECs use and adverse cardiovascular effects, including an increased risk of cardiovascular diseases like myocardial infarction. Nicotine in ECs aerosols can contribute to vascular harm. The effectiveness of ECs as a smoking cessation tool is debated, with many individuals engaging in dual use. ECs use has also been linked to an increased risk of stroke and cerebrovascular diseases. Acrolein, found in ECs products, may trigger oxidative stress and inflammation in the cerebrovascular system. Research suggests that ECs and HTPs use may have brain-toxic effects, resulting in cognitive deficits, epigenetic modifications, and potential neurotoxicity related to solvent carriers like propylene glycol and vegetable glycerin. The safety and risks of inhaling aerosolized vitamin E acetate, found in some ECs products, are poorly understood. Flavorings, particularly attractive to ECs users, especially youth, may have unknown safety profiles when inhaled as aerosols, potentially contributing to cellular and brain toxicity due to their high concentration in e-liquids.